Advancements on mechanically driven two-phase cooling loop systems for data center free cooling. (June 2022) - Gong, Yuexuan; Zhou, Feng; Ma, Guoyuan; Liu, Shuailing
Abstract: Since the onset of the 21st century, the number of data centers has been increasing continuously, and the energy consumption of these data centers has aroused people's attention. Many experiments have been conducted to reduce the energy consumption in data center cooling, and free cooling utilization based on the mechanically driven two-phase cooling loop (MTCL) system has been proven to be an effective solution for energy saving. This paper reviews the research on and developments in the practical application of the MTCL system for data center cooling in recent decades. It presents a detailed summary of the progress of research on the MTCL system in data centers. The aim is to provide an improved understanding of the system and promote the application of this system in data center energy saving.